Respuesta :
Answer:
(6x4 – 7)(6x4 + 7)
Step-by-step explanation:
got 100% on assignment
When we factorise the expression 36x⁸ – 49 completely using a² – b² = (a + b)(a – b), the result obtained is (6x⁴ – 7)(6x⁴ + 7)
Difference of two squares
a² – b² = (a + b)(a – b)
How factorise using difference of two squares
We can factorise the expression 36x⁸ – 49 using difference of two squares as follow:
36x⁸ – 49
Recall
36 = 6²
x⁸ = (x⁴)²
49 = 7²
Thus,
36x⁸ – 49 = 6²(x⁴)² – 7²
36x⁸ – 49 = (6x⁴)² – 7²
36x⁸ – 49 = (6x⁴ – 7)(6x⁴ + 7)
Therefore, the correct answer to the question is (6x⁴ – 7)(6x⁴ + 7)
Learn more about difference of two squares:
https://brainly.com/question/914765